(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The purpose of this paper is to analyze and interpret data coming from a measurement system using the technique of valuation of weights, in order to identify the degrees of intensity in the application of the principles and techniques recommended by the New Public Management (NPM) theory in an electoral competitive environment. We take as analysis period from 1998 to 2008. We exemplified with the municipalities of Culiacan, Sinaloa, where there have been no electoral party substitution in the period considered, and Hermosillo, Sonora and Zacatecas, Zacatecas, which are municipalities in which there has been political substitution in the ruling party. The municipality of Leon, Guanajuato is taken as a role model of municipal government. We conclude that when the ruling party is of conservative nature, a greater emphasis is placed in variables such as organizational structure and regulatory improvement. This is the case of the National Action Party (PAN) in contrast with traditional parties like the Institutional Revolutionary Party (PRI) or leftist organizations such as the Democratic Revolution Party (PRD). All of the municipal governments, regardless of ideology, consider essential to incorporate technologies of information and communication, to improve services. Finally all parties give importance to citizen participation, albeit with different orientation.